Fish tagging data for WorldFish Carp Genetic Improvement Program - Hamilton, Matthew; Akhter, Md (WorldFish, 2024)
This dataset provides the individual identifiers, date of tagging and growth data for catla (Catla catla) and silver carp (Hypophthalmichthys molitrix) spawned in 2024 as part of the WorldFish Carp Genetic Improvement Program